Emotional Reactivity, Self-Control, and Children’s Hostile Attributions over Middle Childhood - Nelson, Jackie A. (Cogn Emot, 2014)
Hostile attribution bias, a child’s tendency to interpret ambiguous social information as threatening or hostile, has been discussed as an important point in which social, emotional, and cognitive information intersect. This study explores the natural changes that occur in children’s hostile attributions across three grades during middle childhood and examines how emotional reactivity and self-control at third, fourth, and fifth grade independently and interactively relate to these trajectories. Participants included 919 children whose mothers reported on their emotional reactivity, whose teachers reported on their self-control, and who completed an attribution bias interview, all at grades 3, 4, and 5. Results revealed that among children with a greater tendency to make hostile attributions at third grade, lower self-control at third grade was associated with greater initial hostile attribution bias and less decline in biases over time. Additionally, greater emotional reactivity at fourth grade was associated with declines in these children’s hostile attributions, but only when self-control was also higher at fourth grade.